1985
DOI: 10.1111/j.1440-1681.1985.tb02637.x
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATIONS INTO THE NATURE OF α2‐ADRENOCEPTORS IN RAT TAIL ARTERIES

Abstract: In rat isolated perfused tail arteries, dose-response curves were established for the vasopressor effects of phenylephrine (alpha 1-adrenoceptor agonist), clonidine (alpha 1- and alpha 2-adrenoceptor agonist), clonidine in the presence of 10(-7) mol/l prazosin (alpha 2-agonist), and BHT-920 (alpha 2-agonist). The ED50 values were: phenylephrine 1.85 X 10(-10) mol; clonidine 6.3 X 10(-10) mol; clonidine + prazosin 3.2 X 10(-6) mol; BHT-920 6.1 X 10(-6) mol. The arterial reactivity to BHT-920 was stable only aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
2

Year Published

1985
1985
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
5
2
Order By: Relevance
“…This point notwithstanding, Weiss et al (1983) showed that in Sprague-Dawley rat tail artery preparations (helical strips), steady-state responses to clonidine were antagonized by low concentrations (10-100 nmol/l) of yohimbine, indicating the presence of ar2-adrenoceptors; this was confirmed in binding studies using tritiated clonidine as ligand. These data stand in direct conflict with the finding of Marwood et al (1985) that yohimbine appeared actually to potentiate rather than antagonize the vasoconstrictor effect of clonidine in the same vessel. Marwood et al (1985) explained the potentiating effect of yohimbine as resulting from an underlying time-dependent increase in sensitivity to the vasoconstrictor effects of clonidine.…”
contrasting
confidence: 65%
See 4 more Smart Citations
“…This point notwithstanding, Weiss et al (1983) showed that in Sprague-Dawley rat tail artery preparations (helical strips), steady-state responses to clonidine were antagonized by low concentrations (10-100 nmol/l) of yohimbine, indicating the presence of ar2-adrenoceptors; this was confirmed in binding studies using tritiated clonidine as ligand. These data stand in direct conflict with the finding of Marwood et al (1985) that yohimbine appeared actually to potentiate rather than antagonize the vasoconstrictor effect of clonidine in the same vessel. Marwood et al (1985) explained the potentiating effect of yohimbine as resulting from an underlying time-dependent increase in sensitivity to the vasoconstrictor effects of clonidine.…”
contrasting
confidence: 65%
“…These data stand in direct conflict with the finding of Marwood et al (1985) that yohimbine appeared actually to potentiate rather than antagonize the vasoconstrictor effect of clonidine in the same vessel. Marwood et al (1985) explained the potentiating effect of yohimbine as resulting from an underlying time-dependent increase in sensitivity to the vasoconstrictor effects of clonidine. It is likely that such an increase in sensitivity to agonists with time is related to the short period of exposure of the tissue to the agonists, since in previous studies in which agonist responses were allowed to stabilize, no such time-dependent increases in sensitivity were noted (Medgett & Langer 1984; Fig.…”
contrasting
confidence: 65%
See 3 more Smart Citations